Managing archives : foundations, principles and practice - Williams, Caroline (Caroline M.) (Chandos information professional series., 2006)
'Managing Archives' is intended to provide up-to-date, practical advice for students and inexperienced professionals starting out in archives with basic guidance sourced from professional literature, standards, websites, etc. The text includes a range of optional test activities.